Hemicentin-1 is an essential extracellular matrix component during tooth root formation by promoting mesenchymal cells differentiation - Cui, Yujia; Li, Chuwen; Wang, Hanyang; Li, Lei; Xie, Jing; Zhou, Xuedong; Zhang, Hai; Sun, Jianxun (Frontiers in Cell and Developmental Biology, 2024)
Root dentin formation is an important process in tooth development. We tried to identify potential genes that regulate root dentin formation which could be potentially used for the regeneration and repair of defective or damaged dental roots. In our study, tissues harvested from the labial and lingual sides of mouse incisors were used for microarray analysis. Gene ontology (GO) analysis of differentially expressed genes indicated the critical role of extracellular matrix in the discrepancy of dentin formation between root and crown, for which hemicentin-1 (Hmcn1) was selected as the target gene. Single-cell RNA sequencing analysis the expression pattern of Hmcn1 at different developmental stages in mouse molars. The spatiotemporal expression of HMCN1 in mouse incisors and molars was detected by immunohistochemical staining. The functions of HMCN1 in human dental pulp cells, including proliferation, differentiation and migration, were examined in vitro by CCK8 assay, BrdU assay, Wound-healing assay, ALP staining and alizarin red staining, respectively. Our results showed that HMCN1 expression was more pronounced in papilla-pulp on the root than crown side in mouse incisors and molars. In vitro experiments presented inhibited dentinogenesis and migration after HMCN1-knockdown in human dental pulp cells, although there was no significant difference in proliferation between the HMCN1-knockdown group and control group. These results indicated that HMCN1 plays an important role in dentinogenesis and migration of pulp cells, contributing to root dentin formation.